Parameters of poor prognosis in preimplantation genetic testing for monogenic disorders. Issue 9 (18th June 2021) - Van Der Kelen, A; Santos-Ribeiro, S; De Vos, A; Verdyck, P; De Rycke, M; Berckmoes, V; Tournaye, H; Blockeel, C; De Vos, M; Hes, F J; Keymolen, K; Verpoest, W
Abstract: STUDY QUESTION: What is the likelihood of success of a single cycle of preimplantation genetic testing for monogenic disorders (PGT-M), measured as the cumulative live birth rate (CLBR) and based on various patient demographics? SUMMARY ANSWER: For all women aged ≤40 years, the CLBR was at least 10% when the number of oocytes was ≥7 (range 10–30%) or was at least 5% when the number of oocytes was ≥3 (range 5–17%). WHAT IS KNOWN ALREADY: The number of oocytes is significantly associated with the number of embryos for genetic testing and the clinical outcome in PGT-M. Embryos diagnosed as affected or embryos that remain without diagnosis cannot be used for embryo transfer. The size of the group of embryos non-suitable for transfer varies between 25% and 81%, depending on the indication. Thus, PGT-M is more likely to be more severely impacted by suboptimal ovarian response, poor fertilization and suboptimal embryo development than conventional IVF/ICSI schemes without PGT. STUDY DESIGN, SIZE, DURATION: This was a single-centre retrospective comparative cohort study, of cycles between January 2011 and December 2015. A total number of 2265 PGT-M cycles were compared to 2833 conventional ICSI cycles. The principal aim of our study was the identification of the parameters of poor CLBR in couples undergoing PGT-M using multiplex short tandem repeat (STR) markers on blastomere biopsy DNA. The secondary aim was to compare the parameters of poor CLBR of the PGT-M population to those of couples undergoing ICSI without PGT. PARTICIPANTS/MATERIALS, SETTING, METHODS: The baseline characteristics of the PGT-M group were compared to the conventional ICSI group. A multiple regression analysis was applied to account for the following potential confounding factors: female age, number of previous ART cycles, number of oocytes/suitable embryos for transfer and dosage of gonadotrophins used for ovarian stimulation. MAIN RESULTS AND THE ROLE OF CHANCE: The PGT-M group was younger (female age 32.0 vs 34.5 years), had a higher number of previous ART cycles (1.1 vs 0.9 cycles) and used more gonadotrophins (2367 vs 1984 IU). Per cycle, the PGT-M group had more retrieved oocytes (11.8 vs 8.3 oocytes), fewer suitable embryos for transfer (1.7 vs 2.8 embryos) and a lower CLBR (29.4% vs 35.0%). Multiple regression analysis showed that the CLBR in the PGT-M group was significantly influenced by female age, the number of previous ART cycles, the number of oocytes and the dose of ovarian stimulation. In both groups, the predicted CLBR increased with increasing numbers of oocytes and suitable embryos. At least two retrieved oocytes or one embryo per single PGT-M cycle could confer an estimated CLBR above 10%. By assessing female age and the number of retrieved oocytes together, it was shown that for all women aged ≤40 years, the predicted CLBR per single PGT-M cycle was ≥10% when the number of oocytes was ≥7 or was ≥5% when the number of oocytes was ≥3. LIMITATIONS, REASONS FOR CAUTION: Despite the large sample size, the findings are confined by limited confounder adjustment and the lack of specific PGT-M comparators. WIDER IMPLICATIONS OF THE FINDINGS: This study aimed to describe the likelihood of success of PGT-M treatment, measured as CLBR, based on various patient demographics. In a PGT-M program, couples need to be informed of the prognosis more specifically when it is futile. The table of predicted CLBRs presented in this study is a useful tool in counselling PGT-M couples for making reproductive choices. STUDY FUNDING/COMPETING INTEREST(S): No funding was required and there are no competing interests. TRIAL REGISTRATION NUMBER: N/A.